Headache and MRI Changes after Endovascular Treatment of a Cerebral Aneurysm. (20th December 2019) - Høllesli, Liv Jorunn; Kurz, Martin W.; Behzadi, Gry Inger N.; Solbakken, Tore; Harald Mørkve, Svein; Kurz, Kathinka D.
Abstract : Background . The main complications after endovascular therapy of intracranial aneurysms are aneurysm rupture and thromboembolic events. Yet, the widespread use of magnetic resonance imaging (MRI) in follow-up of these patients also demonstrates other, rarely known complications such as aseptic meningitis and foreign body reaction. Case Presentation . A small aneurysm in the right posterior communicating artery was treated with endovascular therapy in a 65 year old woman. Two weeks after successful interventional treatment, the patient developed a headache. On MRI performed five months after intervention, vasogenic edema was seen in the vascular territory of the right internal carotid artery. The edema and the symptoms diminished without specific treatment within a year. Interpretation . The clinical and radiological presentation of this case are suggestive of a foreign body reaction, a treatable condition that radiologists and clinicians should be aware of.